ANALISIS SELF EFFICACY PADA DEWASA AWAL DI GPDI EBEN HAEZER WAWALINTOUAN TONDANO - Pelealu, Christine E. E.; Tiwa, Tellma M.; Veronika, Tiara (PSIKOPEDIA, 2025)
This study aims to determine the analysis of self efficacy in early adults at GPdI Eben Haezer Wawalintouan Tondano. The type of research used is qualitative research, with the aim of knowing the role of self-efficacy in early adult individuals in facing service activities at GPdI Eben Haezer Wawalintouan Tondano. The sample used in this study amounted to 4 people. The data collection techniques used are observation, interview and documentation. The results showed that there are several factors that play a role in the formation of self-efficacy of the research subjects, namely direct experience, social persuasion, and physical and emotional conditions. From all the results of the subject interviews, there is one common factor, namely direct experience that forms the self efficacy of each subject. This phenomenon is influenced by factors that contribute to each subject. Keyword : Self Efficacy, Early Adulthood, Services